Four-Corner Arthrodesis with a Dorsal Locking PEEK Plate: A Retrospective Case Series - Hayes, Emmitt; Leswick, David A.; Obaid, Haron; Sauder, David A. (Journal of Wrist Surgery, 2022)
Background Four-corner arthrodesis (4CA) can be performed with a variety of methods. To our knowledge, fewer than 125 cases of 4CA with a locking polyether ether ketone (PEEK) plate have been reported, necessitating further study.Purpose The purpose of this study was to evaluate the radiographic union rate and clinical outcomes in a series of patients who received 4CA with a locking PEEK plate.Methods We re-examined 39 wrists in 37 patients at a mean follow-up of 50 months (median: 52 months, range: 6–128). Patients completed the Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH), Patient-Rated Wrist Evaluation (PRWE), and participated in measurements of grip strength and range of motion. Anteroposterior, lateral, and oblique radiographs of the operative wrist were examined for union, screw breakage and/or loosening, and lunate change.Results The mean QuickDASH score was 24.4 and the mean PRWE score was 26.5. Mean grip strength was 29.2 kg or 84% of the nonoperative hand. Mean flexion, extension, radial deviation, and ulnar deviation were : 37.2, 28.9, 14.1, and 17.4 degrees, respectively. Eighty-seven percent of wrists achieved union; 8% had nonunion; and5% had indeterminate union. There were seven cases of screw breakage and seven cases of screw loosening (as defined by lucency or bony resorption surrounding screws). Twenty-three percent of wrists required reoperation (four total wrist arthrodesis and five reoperations for other reasons).Conclusion 4CA with a locking PEEK plate has clinical and radiographic outcomes similar to other methods. We observed a high rate of hardware complications. It is unclear whether this implant offers a clear advantage over other methods of fixation used in 4CA.Type of Study/Level of Evidence Level IV, therapeutic study.
Keywords: dorsal locking PEEK plate; four-corner arthrodesis; 4CA; wrist arthrodesis; midcarpal joint fusion